(untitled) (Global Journal of Human-Social Science, 2021)
This article intends to argue that the movement of students through the Brazilian mandatory school only acquires signs of an educational political problem from the 1930’s on. It indicates that the current sense of the notion of student failure came to be defined only in the twentieth century, although it was possible to fail students since before. It intends to show further that, in articulation with political and cultural changes in education -such as the emergence of compulsory school, the definition of grade-based model of school, and the primacy of homogeneity of classes -the emergence of better and systematic statistics after 1931 contributed decisively in defining the conditions for the possibility of inclusion of student failure as a problem on the political agenda.